Comparative In Vitro Evaluation of Commercial Periodontal Gels on Antibacterial, Biocompatibility and Wound Healing Ability - Marta Munar-Bestard; Maria Antonia Llopis-Grimalt; Joana Maria Ramis; Marta Monjo (MDPI AG, 2021)
In the last years, several studies testing commercial periodontal gels that contain chlorhexidine (CHX) or other antibacterial agents, have raised concerns regarding their cytotoxicity in periodontal tissues. We aimed at comparing the biocompatibility but also the efficacy as regards to the antibacterial and wound healing ability of different commercial periodontal gels. In vitro human gingival fibroblasts (GF) and a 3D model of human tissue equivalents of gingiva (GTE) were used under inflammatory conditions to evaluate wound closure, cytotoxicity and gene expression. Antibacterial effects were also investigated on Porphyromonas gingivalis growth, viability and gingipain activity. In GF and in the bacterial study, we found cytotoxic effects on GF and a high inhibition on bacterial growth rate in gels containing CHX, asiaticoside, enoxolone, cetylpyridinium chloride, propolis and eugenol. Of the two gels that were non-cytotoxic, Syntoss Biogel (containing chondrontin sulfate) and Emdogain (EMD, containing amelogenin and propylene glycol alginate), EMD showed the best wound closure, with no effect on P. gingivalis growth but decreased gingipain activity. On the other hand, Syntoss Biogel reduced viability and gingipain activity of P. gingivalis, but lack wound healing capacity. In the 3D GTE, Syntoss Biogel and EMD showed a good biocompatibility. Among all the tested gels, formulations containing CHX, asiaticoside, enoxolone, cetylpyridinium chloride, propolis and eugenol showed high antibacterial effect but also showed high cytotoxicity in eukaryotic cells. EMD was the one with the best biocompatibility and wound healing ability at the conditions tested.